English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

-3x = -36 + 7y
-3x + 2y = -36

please explain how you came up with the answer thanks =)

2007-01-29 17:32:57 · 5 answers · asked by Anonymous in Science & Mathematics Mathematics

5 answers

-3x = -36 + 7y
-3x + 2y = -36
so. -3x + 36 = 7y
y = (-3x + 36)/7
then plug in y in the next equation
-3x + 2y = -36
-3x + 2((-3x + 36)/7) = -36
then you do the math yourself

2007-01-29 17:39:54 · answer #1 · answered by Jian H 2 · 0 0

-3x=-36 + 7y
36 = 7y + 3x

36 = 3x - 2y

Subtracting Equation 2 from 1 U get, 0 = 9y so, y= 0.
Now, 36 = 3x + 7(0) or x = 12

2007-01-30 01:43:29 · answer #2 · answered by ArindagR8 1 · 0 0

Rewrite in a form more amenable to solution:
-3x - 7y = -36
-3x + 2y = -36
Multiply the first eqn by -1
3x + 7y = 36
-3x + 2y = -36
Add them
9y = 0 and y=0
Put into the second eqn: -3x + 2(0) = -36
-3x = -36
x = -36/(-3) = 12

2007-01-30 01:40:32 · answer #3 · answered by kellenraid 6 · 0 0

start by rearanging the first equation so that it looks like
3x+7y=36
then add it to the second equation to get
3x+7y=36
-3x+2y=-36
----------------
0x+9y=0
this tells you that y is equal to zero, because if you divide zero by 9 you still get zero
next substitute this value for y into either equation getting
3x+7(0)=36 or -3x+2(0)=-36
then you get either
3x=36 or -3x=-36
divide 36 by 3 which will get you x=18.
so if you are looking for the place where the two equations intersect it will be at the point (18,0).

2007-01-30 01:42:27 · answer #4 · answered by Elizabeth 2 · 0 0

-3x -(-3x + 2y) = -36 + 7y - (-36)

implies

-2y =7y

implies

7y - (-2y) = 9y = 0

implies

y = 0 / 9 = 0

therefore x = ....

for you to find out ....

2007-01-30 01:41:53 · answer #5 · answered by Indrajith 2 · 0 0

fedest.com, questions and answers